Mikrochirurgische Nervennaht: operative Techniken - Ayache, Ali; Langer, Martin Franz; Cavalcanti Kußmaul, Adrian; Unglaub, Frank (Operative Orthopädie und Traumatologie, 2024)
Substantial nerve lesions almost always lead to persistent functional deficits, even with ideal treatment. Nerve lesions commonly occur in young patients, are often part of complex injuries, and are repeatedly diagnosed and treated with delay. Functional outcome crucially depends on early and adequate treatment. The aim of surgical treatment is a precise and tension-free microsurgical restoration of nerve continuity in a vital and healthy tissue environment. Adequate microsurgical treatment with differentiated postoperative treatment can result in an excellent clinical outcome, even after a delayed diagnosis.
Online publiziert: 18. November 2024
Gesehen am 07.04.2025